P-142 Breathe better – feel good, do more. Issue Volume 6: Issue (2016)Supplement 1 (1st November 2016) - Wright, Lisa; Oxberry, Stephen; Crowther, Michael
Abstract : Breathe Better, a palliative chronic lung disease program run over five sessions within the hospice support and therapy centre, was devised as a collaborative initiative between the hospice team, the acute trust, community services and CCG, providing information and practical support signposting patients to hospice services and reducing avoidable hospital admissions. Allowing patients to access hospice services and improve symptom management in end stage disease, changes patients' perceptions and helps to improve quality of life and self-management. Patients are referred to the course via healthcare professionals, have a Medical Research Council Dyspnoea Score of 4 or 5, and are invited to attend with carers. Over the five sessions goal setting is a common theme and continually revisited reinforcing positive achievements and support when required. Sessions include; Medication management, Relaxation and anxiety, Care planning and Fatigue management. Exercises are also completed during each session in a controlled and safe environment. From feedback, patients feel more confident in self-management and ability to perform their daily activities. There has been a significant increase in patients accessing hospice services and recorded future care planning. Patients are achieving their goals and carers report seeing positive differences. Timely input and support is also being given to patients as their condition deteriorates. Importantly, hospital admissions for the six months post Breathe Better are less than half than the six months pre- Breathe Better, at a time when arguably more admissions would be expected. The programme demonstrates that hospices are perfectly placed to address unmet palliative needs for patients with end stage lung disease. We have the skills, expertise and environment to begin to address end-of-life issues with patients and carers and this project demonstrate the huge benefits hospice care can offer this patient group.